Control of water for high-yield and low-cost sustainable electrochemical synthesis of uniform monolayer graphene oxide - Jiaqi Guo; Songfeng Pei; Kun Huang; Qing Zhang; Xizhong Zhou; Jinmeng Tong; Zhibo Liu; Hui-Ming Cheng; Wencai Ren (Nature Communications)
Abstract With the rapid development of graphene industry, low-cost sustainable synthesis of monolayer graphene oxide (GO) has become more and more important for many applications such as water desalination, thermal management, energy storage and functional composites. Compared to the conventional chemical oxidation methods, water electrolytic oxidation of graphite-intercalation-compound (GIC) shows significant advantages in environmental-friendliness, safety and efficiency, but suffers from non-uniform oxidation, typically ~50 wt.% yield with ~50% monolayers. Here, we show that water-induced deintercalation of GIC is responsible for the non-uniform oxidation of the water electrolytic oxidation method. Using in-situ experiments, the control principles of water diffusion governing electrochemical oxidation and deintercalation of GIC are revealed. Based on these principles, a liquid membrane electrolysis method was developed to precisely control the water diffusion to achieve a dynamic equilibrium between oxidation and deintercalation, enabling industrial sustainable synthesis of uniform monolayer GO with a high yield (~180 wt.%) and a very low cost (~1/7 of Hummers’ methods). Moreover, this method allows precise control on the structure of GO and the synthesis of GO by using pure water. This work provides new insights into the role of water in electrochemical reaction of graphite and paves the way for the industrial applications of GO.